2007
DOI: 10.1063/1.2775447
|View full text |Cite
|
Sign up to set email alerts
|

Geometries and stabilities of Ag-doped Sin (n=1–13) clusters: A first-principles study

Abstract: The structures of AgSi(n) (n=1-13) clusters are investigated using first-principles calculations. Our studies suggest that AgSi(n) clusters with n=7 and 10 are relatively stable isomers and that these clusters prefer to be exohedral rather than endohedral. Moreover, doping leaves the inner core structure of the clusters largely intact. Additionally, the plot of fragmentation energies as a function of silicon atoms shows that the AgSi(n) are favored to dissociate into one Ag atom and Si(n) clusters. Alternative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
23
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(30 citation statements)
references
References 30 publications
6
23
1
Order By: Relevance
“…2), which is similar to the favorable structures of Na@Sn 5 0/− , 24 Cu@Si 5 − , 47 and Ag@Si 5 . 51 The VDE of 5A is calculated to be 2.45 eV, which is in accord with the experimental value of 2.49 eV (Table I). A planar structure (5B) is predicted to be 2.37 eV higher in energy than 5A.…”
Section: A Ag@pb 5 −supporting
confidence: 75%
“…2), which is similar to the favorable structures of Na@Sn 5 0/− , 24 Cu@Si 5 − , 47 and Ag@Si 5 . 51 The VDE of 5A is calculated to be 2.45 eV, which is in accord with the experimental value of 2.49 eV (Table I). A planar structure (5B) is predicted to be 2.37 eV higher in energy than 5A.…”
Section: A Ag@pb 5 −supporting
confidence: 75%
“…[27] The lowest energy isomer of Si7Ag + has the edge capped pentagonal bipyramidal structure of Si7 + [27] with the Ag atom at the equatorial position and was previously predicted. [31,32] This structure is similar to that of the cationic Si8 + [27] and to those of Si7Cu + [26] and Si7Mn + . [23] .…”
supporting
confidence: 52%
“…Structures available in the literature for metal doped silicon clusters are taken as initial configurations. [8,26,31,32] A global optimization basin−hopping approach on the BP-86/def-SVP level was applied to search for a large number of possible geometrical arrangements before tighter optimization, for details see ref. [39].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…13 However, it has been found that silicon clusters can be stabilized by doping with transition metal (TM) atoms, [14][15][16] and by now a great number of studies, both experimentally [17][18][19][20][21][22][23][24][25][26][27][28][29] and theoretically, [30][31][32][33][34][35][36] have explored the structures and electronic properties of TM-doped silicon clusters for their potential use in silicon-based nanomaterials. In fact, doping silicon clusters with appropriate transition metal atoms [37][38][39][40][41] can reduce the number of dangling bonds on the cluster surface or even fully saturate them via pd hybridization, and thereby change the geometrical structures and chemical reactivities compared to pure silicon clusters. Accordingly, novel physical and chemical properties of transition-metal doped silicon clusters, e.g., size-specific stability, 30,42 magnetic, 17,28,37,39,43 and optical properties, 44 open up many new and exciting applications, for instance, for silicon-based nano-devices in optoelectronics, tunable lasers, and sensors.…”
Section: Introductionmentioning
confidence: 99%